Pengaruh Keterlibatan Kerja, dan Perceived Supervisor Support Terhadap Organizational Citizenship Behavior dengan Kepuasan Kerja Sebagai Pemediasi - Yuniar Anggita Sari; Ignatius Soni Kurniawan (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the effect of job involvement and perceived supervisor support on organizational citizenship behavior (OCB) with job satisfaction as a mediating variable. This study is a quantitative study using a population of all employees of PT Baja Mulia Industriindo Klaten. Collecting data by census, with a total of 50 respondents using a questionnaire survey. Data analysis using inferential analysis with the statistical program used is Smart PLS 3. The results show that work involvement has an insignificant negative effect on OCB, job satisfaction has an insignificant positive effect on OCB, perceived supervisor support has no significant positive effect on job satisfaction, work involvement significant positive effect on job satisfaction, perceived supervisor support has a significant positive effect on OCB, job satisfaction is able to mediate the relationship between job involvement and OCB, job satisfaction is able to mediate the relationship between perceived supervisor support and OCB.